Legislative Protection for Persons with Disabilities in the Saudi System: A Study in Light of Sustainable Development and Vision 2030 - Abdallah, Ola Ahmed Gaber (Journal of Economic, Administrative and Legal Sciences, 2025)
Globally, recognition of the rights of persons with disabilities has become central to most international and national policies, rather than merely an optional luxury. International texts and treaties on persons with disabilities aim to strengthen efforts to ensure the inclusion of persons with disabilities in all aspects of development efforts and provide an opportunity to strengthen relevant development policies in the implementation of internationally agreed development goals and the achievement of sustainable development for countries, thus contributing to the realization of a “sustainable society for all.” As for the situation in the Kingdom of Saudi Arabia, its legal systems have guaranteed a special status for persons with disabilities by providing comprehensive care services to all those in need of care according to their health condition, degree of disability, or social status. Medical, social, psychological, educational, and vocational services have been employed to help persons with disabilities achieve the highest possible degree of effectiveness within Saudi society, with the aim of enabling them to adapt to the requirements of their natural and social environment, developing their abilities to be self-reliant, and making them productive members of society. The authorities responsible for persons with disabilities in the Kingdom have varied between service, oversight, and regulatory bodies that weave a legislative framework and rules that regulate their work and the responsibilities of each body. The Kingdom updated the system for persons with disabilities in accordance with the latest global developments in 2023 to ensure that it includes all rights recognized by the international community and adopted by the United Nations Sustainable Development Goals, and is consistent with the Kingdom’s Vision 2030.